PERGESERAN PARADIGMA DALAM PENDIDIKAN TINGGI HUKUM (Dari Kurikulum Inti dan Institusional ke Kurikulum Berbasis Kompetensi) - Rini Fidiyani (Faculty of Law, Universitas Jenderal Soedirman, 2010)
The change of era and labor markets creates demand for graduates college of law must have the necessary competency, whereas the high law education system does not prepare graduates to have competencies that are expected. Therefore, a change from the old curriculum to the Competency Based Curriculum (CBC) needs to be done to address these problems. In CBC, competency mapping, teaching paradigm is also shifting from Teacher-Centered Learning (TCL) to the Student-Learning Center (SCL). Loads lecture materials are also change from the original emphasis on technical expertise (academic/hardskills) to the non-technical skills (softskills) are balanced. Expectation with the implementation of CBC on the law of science study program, graduates who can compete and have generated competitiveness in the job market.Keyword: Competency Based Curriculum, Student-Learning Center, Teacher-Centered Learning, hardskills, softskills.